Multi-phase catheter-injectable hydrogel enables dual-stage protein-engineered cytokine release to mitigate adverse left ventricular remodeling following myocardial infarction in a small animal model and a large animal model. (March 2020) - Steele, Amanda N.; Paulsen, Michael J.; Wang, Hanjay; Stapleton, Lyndsay M.; Lucian, Haley J.; Eskandari, Anahita; Hironaka, Camille E.; Farry, Justin M.; Baker, Samuel W.; Thakore, Akshara D.; Jaatinen, Kevin J.; Tada, Yuko; et al.
Highlights: Hydrogels can prolong therapeutic effect of pro-angiogenic cytokines. Current hydrogels are not translatable due to unfavorable mechanical behavior Our novel hydrogel improves translatability for the treatment of cardiac ischemia. Harnessed nanoparticle-polymer interactions for precise mechanics. Achieved dual-stage cytokine release demonstrating distinct delivery profiles. Abstract: Although ischemic heart disease is the leading cause of death worldwide, mainstay treatments ultimately fail because they do not adequately address disease pathophysiology. Restoring the microvascular perfusion deficit remains a significant unmet need and may be addressed via delivery of pro-angiogenic cytokines. The therapeutic effect of cytokines can be enhanced by encapsulation within hydrogels, but current hydrogels do not offer sufficient clinical translatability due to unfavorable viscoelastic mechanical behavior which directly impacts the ability for minimally-invasive catheter delivery. In this report, we examine the therapeutic implications of dual-stage cytokine release from a novel, highly shear-thinning biocompatible catheter-deliverable hydrogel. We chose to encapsulate two protein-engineered cytokines, namely dimeric fragment of hepatocyte growth factor (HGFdf) and engineered stromal cell-derived factor 1α (ESA), which target distinct disease pathways. The controlled release of HGFdf and ESA from separate phases of the hyaluronic acid-based hydrogel allows extended and pronounced beneficial effects due to the precise timing of release. We evaluated the therapeutic efficacy of this treatment strategy in a small animal model of myocardial ischemia and observed a significant benefit in biological and functional parameters. Given the encouraging results from the small animal experiment, we translated this treatment to a large animal preclinical model and observed a reduction in scar size, indicating this strategy could serve as a potential adjunct therapy for the millions of people suffering from ischemic heart disease.